2013
DOI: 10.1002/mrd.22278
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly cleaving bovine two‐cell embryos have better developmental potential and a distinctive mRNA pattern

Abstract: Mammalian embryos that rapidly reach the two-cell stage in culture have a higher probability of becoming viable blastocysts. Our goal was to separate two-cell bovine embryos based on their zygotic cleavage timing, and to assess their global mRNA levels. Following in vitro fertilization, all embryos that cleaved by 29.5 hpi (early) were cultured separately from those that divided at 46 hpi (late). The blastocyst rates were 46.1 ± 3.7% and 6.1 ± 3.4% for early- and late-cleavers, respectively (P < 0.01). Seven r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 75 publications
3
27
0
1
Order By: Relevance
“…; Orozco‐Lucero et al. ) establishing that the early cleaving IVF embryos are more likely to develop to the blastocyst earlier and that they are likely to have better quality compared to late cleaving IVF embryos. In humans, extensive studies have been conducted to correlate the time of cleavage with the developmental competence of IVF embryos (Fenwick et al.…”
Section: Discussionmentioning
confidence: 99%
“…; Orozco‐Lucero et al. ) establishing that the early cleaving IVF embryos are more likely to develop to the blastocyst earlier and that they are likely to have better quality compared to late cleaving IVF embryos. In humans, extensive studies have been conducted to correlate the time of cleavage with the developmental competence of IVF embryos (Fenwick et al.…”
Section: Discussionmentioning
confidence: 99%
“…Mature oocytes can form a new zygote and continue to develop after combining with male gametes, and the original maternal genetic control can convert to embryonic genetic control, that is maternal-toembryonic transition (MET). The early cleavage divisions time was related to embryonic development potential, as evidenced by the higher developmental competence of early cleaved embryos compared to that of late cleaved embryos (Luo et al 2010;Isom et al 2012;Orozco-Lucero et al 2014). Previous studies have shown that the follistatin (FST) gene may be a maternal gene and that messenger RNA (mRNA) abundance of FST in oocytes has a positive relationship with developmental potential of oocytes (Patel et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Such in silico assessment placed CDKN1A (Cyclin Dependent Kinase Inhibitor 1A) as a putative upstream regulator (data not shown). This cyclin‐dependent kinase inhibitor is also a candidate upstream regulator in fast‐cleaving 2‐cell bovine embryos (Orozco‐Lucero et al, ), further supporting the model that translational control is associated with developmental competence. CDKN1A is, in turn, modulated by TP53.…”
Section: Discussionmentioning
confidence: 71%
“…Interestingly, Labrecque, Vigneault, Blondin, and Sirard () reported that mRNAs abundance of at least 13 translation initiator factors (including EIF3G , EIF1AD , EIF3C , EIF4E1B , EIF5A , EIF4A2 , and EIF2G ) as well as two poly(A)‐binding proteins ( PABPN1 and PABPC1L ) differs in germinal vesicle‐stage oocytes, according to their quality, from cows subjected to a follicle stimulating hormone superstimulation‐and‐withdrawal protocol. EIF5A2 and EIF2AK4 transcript abundances were also higher in the most‐viable 2‐cell bovine embryos (Orozco‐Lucero et al, ). Therefore, a higher abundance of specific factors in the most‐competent oocytes or early embryos likely provides improved translational capacity, which may account for the increased protein synthesis during cleavage or temporal translational inhibition until a particular protein is required (Figure ).…”
Section: Discussionmentioning
confidence: 97%